Biocatalytic upgrading of unconventional crude oil using oilfield-inhabiting bacterial consortia. (October 2022) - Abdul Raheem, Abdul Salam; Hentati, Dorra; Bahzad, Dawoud; Abed, Raeid M.M.; Ismail, Wael
Abstract: We enriched several bacterial consortia from oilfield samples and investigated them for heavy crude oil biocatalytic upgrading potential. SARA (Saturates, Asphaltenes, Resins, Aromatics) analysis of heavy oil treated with one bacterial consortium (designated as 5C) revealed up to 127% increase in the saturates fraction, accompanied by 54% decrease in the aromatics fraction. The asphaltene content was reduced by 52% and the resins increased by 87%. SimDist analysis revealed a better average recovery of fractions from the biotreated oil (up to 86%) compared to the non-treated oil (71%), and the biotreated oil from one culture was fully recovered. While Ni and V contents were mostly higher (up to 125%) in the biotreated oil compared to untreated controls, sulfur content marginally dropped (up to 3.5%) after biotreatment. Illumina-MiSeq amplicon sequencing uncovered source-dependent variations in the composition of the bacterial consortia, with Proteobacteria, Actinobacteria, Bacteroidia and Bacilli as the most abundant in all cultures (≥98.7% of total sequences). The structure of the bacterial consortia shifted with time, revealing different members potentially involved in the bioupgrading process. In the 5C culture, Achromobacter and Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium appeared to be key players. It can be inferred that biocatalytic hydrocarbon redistribution in the biotreated oil improved distillation efficiency. Graphical abstract: Image 1 Highlights: Heavy crude oil-upgrading bacterial consortia were obtained from oilfields. Bioupgrading of heavy crude oil via hydrocarbon redistribution. Enhanced distillation profile after crude oil biotransformation. Temporal shifts in the bacterial communities composition occur during crude oil upgrading.